Clustering analysis and key drivers of tourism village sustainability: evidence from The Mountain Merapi Tourism Area, Indonesia - Aulia Hapsari Juwita; Akhmad Fauzi; Ernan Rustiadi; Wiwiek Rindayati (Regional Development Information Center, Universitas Sebelas Maret, 2026)
This study aims to determine the factors contributing to the sustainability of tourism villages in the Mount Merapi tourism area, Special Region of Yogyakarta, Indonesia. This research applies Matrix of Cross Impact Multiplication Applied to a Classification (MICMAC). Thirty tourism villages were grouped into two clusters: Cluster A, representing villages with limited tourism infrastructure, and Cluster B, representing villages with better-developed infrastructure. The identification results revealed 24 sustainability variables grouped into five dimensions: economic, social, institutional, environmental, and technological. The analysis revealed that Cluster A and Cluster B share similar key drivers for village tourism sustainability, including social capital and government role. The dependent variables in quadrant III are tourist numbers, agricultural technology, cleanliness, financial reserves, early warning technology, and community disaster response. Based on the synthesis of MICMAC results, intrinsic sustainability characteristics of tourism village are endowment, built-in, and inventory.